THE IMPACT OF PARENTAL MENTAL VIOLENCE ON THE PSYCHOLOGICAL CONDITION OF EARLY CHILDHOOD - Imey, Nur Ima; Arisanti, Kustiana; Kiromi, Ivonne Hafidlatil (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Psychological violence has a negative impact on early childhood. Many families cover up violence against young children in front of other people because they think it is their right to privacy. The purpose of this research is to explore the causes of psychological violence in young children in the family. The data in this article is presented descriptively which indicates a scientific study that can be further developed and applied. The object of writing a description in this article is about the problem of the impact of parental mental violence on the psychological condition of early childhood. The technique used in data collection begins with collecting relevant references, both in the form of written texts and soft copy editions, such as scientific journals, ebooks, online articles, and government publications. Soft copy edition references can be obtained from internet sources accessed online. After searching for references that are relevant to the data needed, then the authors analyze the existing data. The results of this study are children who experience mental violence have a tendency to imitate the behavior of their parents. Children will be more aggressive towards their peers. The child will transfer his aggressive feelings to his friends as a result of poor self-concept. This of course will also have an impact on social relations. Children prefer to be alone, have few friends, and enjoy disturbing adults. Examples of disturbing adult behavior such as throwing stones or other criminal acts.